A qualitative study of 2Create: A mental health service user-led art group. Issue 2 (3rd May 2016) - Wilson, Ceri; Kent, Lyn
Background: 2Create is a mental health service user-led art group in the UK, established by graduates of Open Arts, a community arts and mental health project. The study aimed to explore group members' experiences over its first year.Methods Semi-structured interviews were conducted with five current and one former member of 2Create.Results Key themes related to organisation (evolving, flexibility, finance, leadership challenges), the studio environment, personal gains (social inclusion, self-esteem, well-being) and future plans (increasing membership, exhibitions, funding applications, social events).Conclusion The gains reported indicate that 2Create is beneficial to its members. Although a number of challenges were identified, all participants identified personal and group-wide gains and emphasised that challenges are to be expected when setting up a new group. The key implication for independent mental health user-led arts groups is that support is needed in the early stages, and that independence can then be achieved with time.